THE CHALLENGES OF RUNNING MAGNETIC RESONANCE IMAGING SERVICES IN THE TERTIARY HEALTH CENTERS OF NIGERIA - SAIDU SA; UMAR FK (Ntec Specialist, 2016)
The field of diagnostic radiology has emerged and expanded to become an integral part of healthcare worldwide. Nigeria, as a country is keeping pace with the global trend. Magnetic resonance imaging (MRI) is now becoming standard clinical care in many tertiary health centers of Nigeria. The technique has great advantages and some setbacks in a country like Nigeria. Here, we review some of the challenges involved in the practice of MRI, including recommendations on the way forward for overall advancement of MRI services in the country. Method: Literature search were done using keywords described above on Medline, PubMed, HINARI and Advanced Google search. Relevant articles were pooled and information was extracted and appropriately referenced. Books and Journal hard copies were also obtained from the Library of Usmanu Danfodiyo University Teaching Hospital, Sokoto. These were referenced accordingly. Results: The introduction of MRI as a radiological modality in Nigeria revolutionized the field of medicine. MRI gives different, reliable, safer and superior information when compared with X rays (radiography) and computed tomography (CT) scans especially as regards soft tissue differentiation. The foremost challenges of MRI in Nigeria are; high economic cost, poor power supply issues and technical maintenance. Conclusion: We recommend a multi stakeholder approach in areas of procurement, installation, training and maintenance of MRI machine. The national health insurance scheme and other hospital based welfare schemes should be expanded to significantly accommodate high cost investigations like the MRI